A Resonant Pressure Microsensor with a Wide Pressure Measurement Range - Chao Xiang; Yulan Lu; Chao Cheng; Junbo Wang; Deyong Chen; Jian Chen (Micromachines, 2021)
This paper presents a resonant pressure microsensor with a wide range of pressure measurements. The developed microsensor is mainly composed of a silicon-on-insulator (SOI) wafer to form pressure-sensing elements, and a silicon-on-glass (SOG) cap to form vacuum encapsulation. To realize a wide range of pressure measurements, silicon islands were deployed on the device layer of the SOI wafer to enhance equivalent stiffness and structural stability of the pressure-sensitive diaphragm. Moreover, a cylindrical vacuum cavity was deployed on the SOG cap with the purpose to decrease the stresses generated during the silicon-to-glass contact during pressure measurements. The fabrication processes mainly contained photolithography, deep reactive ion etching (DRIE), chemical mechanical planarization (CMP) and anodic bonding. According to the characterization experiments, the quality factors of the resonators were higher than 15,000 with pressure sensitivities of 0.51 Hz/kPa (resonator I), −1.75 Hz/kPa (resonator II) and temperature coefficients of frequency of 1.92 Hz/°C (resonator I), 1.98 Hz/°C (resonator II). Following temperature compensation, the fitting error of the microsensor was within the range of 0.006% FS and the measurement accuracy was as high as 0.017% FS in the pressure range of 200 ~ 7000 kPa and the temperature range of −40 °C to 80 °C.